The Littlest Library : a novel - Alexander, Poppy (New York : Avon, an imprint of HarperCollins Publishers, 2022)
"Jess Metcalf is perfectly content with her quiet, predictable life. But when her beloved grandmother passes away and she loses her job at the local library, Jess life is turned upside down. Determined to pick up the pieces, Jess decides it s time for a new beginning. Unable to part with her grandmother s cherished books, she packs them all up and moves to a tiny cottage in the English countryside. To her surprise, Jess discovers that she s now the owner of an old red phone box that was left on the property. Missing her job at the local library, Jess decides to give back to her new community using her grandmother s collection to turn the ordinary phone box into the littlest library in England. It s not long before the books are borrowed and begin to work their literary magic bringing the villagers together... and managing to draw Jess grumpy but handsome neighbor out of his shell. Maybe it s finally time for Jess to follow her heart, let go of her old life, and make the village her home? But will she be able to take the leap?" --back cover.
new book 2023 summer.
Publication date from publisher's website.
Keywords: Women librarians -- Fiction -- Dismissal; Grandmothers -- Fiction -- Death; Little free libraries -- Fiction; Village communities -- Fiction; Books and reading -- Fiction; Neighbors -- Fiction; England -- Rural conditions -- Fiction; Domestic fiction; Romance fiction